Comparative Analysis of Full Costing and Variable Costing in Larangan Pamekasan Batik Craftsmen - Septia Catriani (Monex: Journal of Accounting Research, 2026)
The purpose of this study is to evaluate and differentiate between the full costing and variable costing approaches in calculating profit and production costs. This research employs a qualitative descriptive methodology, with data collected through direct interviews with batik artisans, observation of the production process, documentation. For the batik artisans in Larangan Badung Pamekasan, both full costing and variable costing methods allow them to select the approach that best suits their needs. According to the study’s findings, the full costing method results in higher production costs as it accounts for both fixed and variable costs, whereas the variable costing method considers only variable costs. Consequently, full costing leads to lower profits. Calculations show that production costs under full costing are higher than those under variable costing, resulting in significantly different profits for the artisans. This difference serves as a reference for choosing a cost determination method, which directly affects the artisans’s profit outcomes. Therefore, it is recommended that batik artisans understand the characteristics of each method to avoid making incorrect decisions that could lead to business failure. The study is expected to assist artisans in selecting the appropriate method to ensure the sustainability of their business.